New Asian Andrena species, with notes on the subgenus Cnemidandrena (Hymenoptera: Andrenidae) - Wood, T.j. (Zootaxa, 2024)
Asia is the world’s largest continent and comprises most of the Holarctic biogeographic region. The genus Andrena is principally distributed through the Holarctic, but it remains understudied in Asia. The subgenus Cnemidandrena Hedicke, 1933 is distributed across Asia with some species reaching south to the Tibetan Plateau. However, some southern members display an unusual morphology, including A. (Cnemidandrena) kishidai chagyabensis Wu, 1982 (newly recorded for Bhutan, India, and Nepal) and A. (Cnemidandrena) granulitergorum Tadauchi & Xu, 2002 (newly recorded for Nepal). The male of A. granulitergorum is described for the first time, A. (Cnemidandrena) rufina Morawitz, 1876 is reported from Kyrgyzstan, Afghanistan, and Kashmir for the first time, and possible senior synonyms for Asian A. (Cnemidandrena) are suggested. To contribute to an improved understanding of localised Asian Andrena diversity, the following new species are described: A. (Cnemidandrena) textrix sp. nov. from China, A. (incertae sedis) liebigi sp. nov. and A. (Troandrena) monfaredi sp. nov. from Iran, and A. (incertae sedis) quercorum sp. nov. from Turkey. These results further confirm that additional taxonomic work is needed to harmonise Andrena species concepts across the different biogeographic regions of Asia.